ANALYSIS OF THE ACCOUNTABILITY OF CRIMINAL ACTIVITIES IN THE EIGHT OF THE LUWAK POWDER COFFEE IN PD. SUMBER BUANA ABADI (Study of Decision Number 307 / Pid.B / 2018 / PN.Kla) - Pratama, Ari (Progressive Law Review, 2019)
One form of embezzlement is in the Decision of the Kalianda District Court of South Lampung Number 307 / Pid.B / 2018 / PN.Kla which states that Defendant Selamet Riyadi Bin Tugino has been proven legally and convincingly guilty of committing a criminal offense